Amok at schools: prevention, intervention and aftercare in school shootings - Böhmer, Matthias (Springer, 2023)
1. definition and typology -- 2. selected school shootings worldwide -- 3. causes -- 4. characteristics of the crime (motives, process) -- 5. preventive measures -- 6. interventions -- 7. aftercare 8. trauma therapy for acutely traumatised persons in the context of a trauma outpatient clinic.